The Influence Of Consumptive Behavior, Overconfidence, And Loss Aversion On Stock Investment Decisions With Risk Tolerance As An Intervening Variable - Cilci, Riri Fitria; Safitri, Heni; Hariyanto, Dedi (UNIVERSITAS PAKUAN, 2025)
This study aims to examine the effect of consumptive behavior, overconfidence, and loss aversion on stock investment decisions, with risk tolerance as a mediating variable. Using a quantitative associative approach with PLS-SEM analysis, data were collected from 150 active investors in Pontianak City who had at least one year of stock investment experience. The results show that loss aversion and risk tolerance have a direct and significant influence on investment decisions. Investors who tend to avoid losses and have higher risk tolerance are more likely to make investment decisions. Meanwhile, consumptive behavior and overconfidence showed a positive but insignificant influence, indicating they do not strongly drive investment actions. In terms of indirect effects, risk tolerance significantly mediates the relationship between overconfidence and investment decisions, as well as between loss aversion and investment decisions. However, no significant mediation was found between consumptive behavior and investment decisions. These findings highlight the dominant role of psychological factors particularly risk perception and aversion in shaping investment behavior. Understanding these aspects is essential for designing financial education strategies aimed at improving decision-making quality among investors.